Optimizing Digital Zakat for Poverty Alleviation: Evidence from Dompet Dhuafa Banten - Palmawati Tahir; Riskiani Riskiani (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2026)
Persistent poverty continues to challenge sustainable development in Indonesia, underscoring the need for innovative mechanisms that strengthen the effectiveness of Islamic social finance. Although digital technologies have transformed charitable giving, limited empirical attention has been paid to how digitalization enhances the institutional performance of zakat organizations and contributes to poverty alleviation. This study examines the optimization of digital zakat at Dompet Dhuafa Banten and evaluates its role in improving fundraising capacity and the delivery of social assistance. Employing a mixed normative and empirical juridical approach with qualitative analysis, the study combines a review of the legal framework governing zakat management with an examination of ZISWAF fundraising data from 2023 to 2025. The findings show that digital payment platforms, QRIS integration, and digital communication strategies significantly increased zakat collection, from IDR 3.48 billion in 2023 to IDR 5.47 billion in 2025, while also enhancing transparency and accelerating the distribution of assistance to beneficiaries (mustahik). This study contributes to the literature on Islamic social finance by demonstrating that digital transformation strengthens institutional accountability and operational efficiency, thereby positioning digital zakat as a sustainable instrument for poverty alleviation and inclusive social welfare.